2014
DOI: 10.1021/la404017q
|View full text |Cite
|
Sign up to set email alerts
|

High Photocatalytic Activity of Transparent Films Composed of ZnO Nanosheets

Abstract: Nanometric thin films were prepared by dip-coating and inkjet printing ZnO nanosheets on glass plates. The side-by-side alignment of the ZnO nanosheets on the substrate resulted in thin, transparent, oriented ZnO surfaces with the high-energy {001} facets exposed. The method of nanosheet deposition affected the film morphology; the dip-coated films were very smooth and nonporous, while the inkjet-printed films were rough and porous with the estimated void volume approximately 60-70% of the total film volume. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…The restored OH radical can either further oxidize the primary ring opening product or attack another molecule of 4-chlorophenol. These DFT results were in good agreement with the photocatalytic degradation experiments conducted using both ZnO and TiO 2 photocatalysts [23,27]. According to the parallel mechanism, the products of 4-chlorophenol degradation are the experimentally identified aromatics hydroquinone and benzoquinone, as well as various ring-opening compounds formed under the restoration of OH radicals (Figure 4a).…”
Section: Photocatalytic Performance Of Rgo/tio 2 Layerssupporting
confidence: 82%
See 3 more Smart Citations
“…The restored OH radical can either further oxidize the primary ring opening product or attack another molecule of 4-chlorophenol. These DFT results were in good agreement with the photocatalytic degradation experiments conducted using both ZnO and TiO 2 photocatalysts [23,27]. According to the parallel mechanism, the products of 4-chlorophenol degradation are the experimentally identified aromatics hydroquinone and benzoquinone, as well as various ring-opening compounds formed under the restoration of OH radicals (Figure 4a).…”
Section: Photocatalytic Performance Of Rgo/tio 2 Layerssupporting
confidence: 82%
“…To explain the mechanism of 4-chlorophenol photocatalytic degradation, in our previous studies, we employed experimental and theoretical, using density function theory (DFT), approaches. Our results therein showed that the hydroxylation and opening of the aromatic ring can occur in parallel with the release of the hydroperoxyl and hydroxyl radicals [23,27]. The restored OH radical can either further oxidize the primary ring opening product or attack another molecule of 4-chlorophenol.…”
Section: Photocatalytic Performance Of Rgo/tio 2 Layersmentioning
confidence: 65%
See 2 more Smart Citations
“…In fact, this ratio shows a direct correlation with the trend followed by app , indicating again that the nanoflake morphology is more photoactive because a greater number of active facets are exposed to the dye molecules and to the UV light. Other authors have found similar results, in which nanoplatelets, nanosheets, or crystals with a large (100)/(002) XRD planes intensity ratio have higher photocatalytic activity than the nanorod morphology [44][45][46], and attributed this behavior to the presence of a major proportion of polar faces. Analyzing deeper the surface-to-volume ratio of the nanorod structures, it is possible to observe that as the dimensions of the rod decrease (length and radius), the surface-to-volume ratio increases, while for larger dimensions this ratio rapidly decreases.…”
Section: Resultssupporting
confidence: 56%